MIKULICZ'S SYNDROME ASSOCIATED WITH LEUKEMIA: A CASE REPORT - Elitsa Deliverska; Lutchezar Stefanov; Evgueniy Hadjiev; Zornitsa Mihaylova; Dobrina Karayasheva (Peytchinski Publishing, 2018)
Mikulicz's syndrome is a chronic swelling of the lacrimal and major salivary glands usually associated with significantly decreased or lack of lacrimation and xerostomia, accompanied by lymphocytic infiltration. It is associated with other entities like tuberculosis, lupus erythematosus, lymphoma, leukemia, etc. A case of 70 years old man with painless, dense swelling of the left parotid gland and medical history of leukemia is presented. The decreased secretory activity of the parotid gland is observed. The patient is referred for laboratory blood test and ultrasound examination of the parotid glands. Mikulicz's syndrome associated with acute myelogenous leukemia was identified. Laboratory blood test reveals leukocytosis (118 g/L). The progress of the glands pathology seems to be associated with the severity of the main disease and appears to be a poor prognostic sign. Based on the findings the definitive diagnosis in the reported case is Mikulicz's syndrome associated with leukemia. The swelling is expected to disappear spontaneously or after treatment with corticosteroids. However, paliative treatment was conducted due to the severity of the systemic disease.